KINERJA KARYAWAN PADA CV DIMAS PRASETYA PALEMBANG - Wayan Jane; Lin Yan Syah; Rabin Ibnu Zainal (Jurnal Manajemen Bisnis Unbara, 2021)
EMPLOYEE PERFORMANCE AT CV DIMAS PRASETYA PALEMBANG. Jl. Lt. Col. Iskandar No. 630 Floor I. Tel. 310679. This study aims to determine the level of employee performance at the company CV Dimas Prasetya Palembang. This study uses two types of data, namely primary and secondary data, while the research method involves employee performance and data analysis in data collection, data reduction and data presentation. In addition, researchers use fishbone diagram data analysis methods (fishbone diagrams). From the results of the analysis, researchers know that the condition of employee performance at CV Dimas Prasetya Palembang has decreased employee performance due to lack of quality and low ability to cooperate or company effectiveness which is the result of decreasing employee performance at CV Dimas Prasetya Palembang. So that the performance of employees at the company is not good.